Kajian Bahan Bimbingan dan Konseling dalam Serat Wedhatama - Sutarno, Sutarno; Barida, Muya (Jurnal Kajian Bimbingan dan Konseling, 2017)
School Counselor or Counselor have to perform professional guidance and counseling services, such as developing guidance and counseling materials from various sources including international, national, and local sources. The purpose of this study is to obtain the guidance and counseling materials contained in the Serat Wedhatama which contains the teachings about morals and virtuous as a source of local teaching. This qualitative research using ethnographic model and explorative content analysis procedures, with a content analysis procedure. Results show that the teachings contained inside Serat Wedhatama are the values and teachings of virtuous morals that can be used as guidance and counseling materials, and can be packaged in the composition of information services and library display.